A literary experiment of the Cold War in the Hispanic world: Comiendo en Hungría - Sanchez, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2024)
In 1969, Miguel Ángel Asturias and Pablo Neruda jointly signed that curious literary-gastronomic experiment that is Comiendo en Hungría, a summary of their trip to the Hungarian country, which is also one of the least known texts of both authors. The purpose of this paper is to analyze the unrepeatable exceptionality of this text, which involves a sum of international efforts of socialist sign (including a Spanish and a Hungarian publisher) that, despite its apparent triviality, is of marked interest for the understanding of the relationship of literary forces in the cultural Cold War, at a moment as special as it was, in addition, the boom of Latin American narrative. The conditions of its production, the relationship with previous works of the two authors and the ideological elements present in the text are analyzed. This is intended to contribute to the understanding of the cultural strategies of real socialism in the Hispanic sphere.